Monet in acrylics - Gregory, Noel (Ready to paint the masters, 2010)
Shows how to reproduce four famous paintings by Claude Monet and one inspired by the master, using acrylic paints. This book contains the step-by-step photographs and instructions. It features the reusable tracings that make replicating Monet's free, expressionistic works simple by showing you the basic shapes with which to experiment.